"Music, singing, word, action": the Opera-Dramatic Studio 1935–1938. Issue 1 (2nd January 2023) - Shevtsova, Maria
ABSTRACT: Central preoccupations of Stanislavsky's theatre practice and thought involve continuous laboratory explorations, revisions and developments. What emerges as new at one time is constantly renewed, indicating that his work of perpetual change raises the question as to what actually were the defining achievements of the Opera-Dramatic Studio. This was the last of the seven studios that Stanislavsky founded and led, or encouraged and protected under the flagship of the Moscow Art Theatre as he taught to varying degrees in each. The discussion here rejects the commonplace idea that Stanislavsky discovered the "method of physical action" in the closing years of his life, showing earlier avatars of "physical action" while unfolding its different but interconnected aspects, including "word action." Stanislavsky's comprehensive approach to acting together with his intensive research on the actor-singer, music, movement, vocalization and other components that bind opera and dramatic theatre gave the Opera-Dramatic Studio its unique identity.